G522(P) The role of inpatient assessment of problematic severe asthma. (27th April 2016) - Gambhir, N; Longman, J; Nagakumar, P; Hall, P; Saglani, S; Bush, A; Fleming, L
Abstract : Introduction: A structured out-patient assessment of children with problematic severe asthma (PSA) differentiates difficult (DA) from true severe therapy resistant asthma (STRA)(Bracken: ADC: 2009) and addressing the basics of management leads to long term benefits (Sharples: ERJ: 2011). However, a small number of children continue to cause concern, particularly when reported symptoms are discrepant with objective measures. We hypothesised that these children would benefit from in-patient assessment. Aim: To assess the role of inpatient observation, investigations and detailed multidisciplinary assessment of patients with PSA. Methods: Observational retrospective analysis of 26 children with PSA admitted to a tertiary referral centre during 2012–2014. Children were admitted for up to 20 days of supervised therapy and observation. All children participated in a daily physiotherapy led exercise programme and were offered psychological support. Spirometry and exhaled nitric oxide (FeNO) were measured twice weekly. Results: 26 children aged 6–15 years were included (Table 1 ). Exhaled nitric oxide (FeNO) and FEV1 improved significantly from admission to discharge (38 ppb vs 20.7 ppb, p = 0.007 and 92 vs 99% predicted, p = 0.003 respectively) likely reflecting improved adherence (Figures 1 and 2). The information gained as part of the admission had a significant impact on the management of most patients: 6 patients were referred to social services due to concerns regarding adherence to medications at home or over reporting of symptoms 8 children had normal lung function, were asymptomatic, and required no salbutamol during the in-patient stay despite high levels of symptom reporting. Asthma medications were weaned either at discharge or at follow up 6 children were diagnosed with a breathing pattern disorder 8 children were found to have significant psychological issues and were referred for further management (Some children appear in more than one of these categories.) Discussion: Valuable objective insights can be gained as part of a prolonged in-patient stay in children with problematic severe asthma. An admission should be considered in those with a discrepancy in the severity of reported symptoms and objective evidence of severe disease, particularly where there are safeguarding concerns.